English Teachers’ Strategy in Implementing the Independent Curriculum in EFL Classroom at Senior High Schools in Barru - Ayu Sasra; Magdahalena Tjalla; Zulfah Fakhruddin; Abdul Haris Sunubi; Ambo Dalle (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
The implementation of Independent Curriculum in English learning in school is a significant step in promoting education that is more student-centered, inclusive and relevant. The curriculum gives opportunity to the students to foster creativity and better English proficiency. This research aims to describe how the implementation of independent curriculum in EFL classroom in accordance to determine the proper teaching strategy that the English teachers apply in the classroom. This research used a descriptive qualitative approach to get the data in the form of interview, observation and documentation. The results showed that English teachers in each school which was the subject of this research used a variety of strategies in teaching English in the classroom. Most of these strategies still used the conventional one even though the learning curriculum has changed. This was due to the lack of knowledge, training, and experience about this independent curriculum. Although the independent curriculum has been launched since February 2022, in fact there were still many schools that have not implemented this curriculum along with teachers who do not understand the intricacies of this independent curriculum.